2023
DOI: 10.1101/2023.10.30.564764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A statistical framework for powerful multi-trait rare variant analysis in large-scale whole-genome sequencing studies

Xihao Li,
Han Chen,
Margaret Sunitha Selvaraj
et al.

Abstract: Large-scale whole-genome sequencing (WGS) studies have improved our understanding of the contributions of coding and noncoding rare variants to complex human traits. Leveraging association effect sizes across multiple traits in WGS rare variant association analysis can improve statistical power over single-trait analysis, and also detect pleiotropic genes and regions. Existing multi-trait methods have limited ability to perform rare variant analysis of large-scale WGS data. We propose MultiSTAAR, a statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Previous studies on non-coding rare variants and lipid traits found that ∼32% signals are independent of common variants, although a more lenient association cutoff was used (P<1.2e -3 , Bonferroni multiple test correction over 43 tests) 48 . A more recent approach on the same traits indicated that only ∼8% non-coding associations were independent, more in line with our results 51 . Regarding CDS regions, we observed that ∼40% CDS gene-trait associations are independent from known GWAS common variants, a large increase compared to non-coding regions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Previous studies on non-coding rare variants and lipid traits found that ∼32% signals are independent of common variants, although a more lenient association cutoff was used (P<1.2e -3 , Bonferroni multiple test correction over 43 tests) 48 . A more recent approach on the same traits indicated that only ∼8% non-coding associations were independent, more in line with our results 51 . Regarding CDS regions, we observed that ∼40% CDS gene-trait associations are independent from known GWAS common variants, a large increase compared to non-coding regions.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, we took a conservative approach by only considering a subset of 42 traits for which we had successfully obtained independent GWAS hits, whereas other studies might deem a rare variant association independent if no nearby GWAS hits are present 10 . Moreover, we performed conditional analysis across all possible gene-trait pairs and performed multiple test correction accordingly, whereas other studies only performed conditional analysis and multiple test correction on a subset of previously significant gene-trait associations 47,48,51 . Regarding traits, a study on 9 red blood phenotypes, which encompassed both coding and non-coding variants, determined that only 13% single variant-trait associations are independent from common variants 49 , suggesting estimates of independence may be lower for some blood cell traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations